MRI of Osteoarthritis: The Challenges of Definition and Quantification - Hayashi, Daichi; Guermazi, Ali; Roemer, Frank W. (Seminars in Musculoskeletal Radiology, 2012)
The ability of MRI to visualize the joint as a “whole organ” and to directly and three-dimensionally assess cartilage morphology and composition has given it a crucial role in discovering the natural history of osteoarthritis (OA). Morphological analysis can be semiquantitative or quantitative. Compositional analysis such as delayed gadolinium-enhanced MRI of cartilage and T2 mapping allows quantitative evaluation of tissue ultrastructure and can detect premorphological changes of cartilage and other tissues. Contrast-enhanced MRI can accurately assess the true extent of synovial inflammation. Most MRI-based studies so far have focused on knee OA, but with the availability of new semiquantitative scoring systems for hand and hip OA, studies of these joints have begun to appear. Because of the technical complexity of MRI and ever increasing number of new and sophisticated imaging sequences and protocols, the specific MRI technique in any OA study needs to be carefully tailored to the aims of the study.
Keywords: osteoarthritis; MRI; knee; semiquantitative; quantitative; scoring